1983
DOI: 10.1159/000280879
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisin ‘Abacterial’ P Prostatitis: Microbiological, Cytological and Serological Studies

Abstract: Chlamydia trachomatis was isolated from urethral swabs after prostatic massage in patients with 'abacterial' prostatitis. After exclusion of prostatic infections by gram-negative bacteria, enterococci and ureaplasmas, in 20 of 43 patients with apparent monoinfection by C. trachomatis, a leucocytal reaction was demonstrated in prostatic secretions. By microimmunofluorescence test, antibody titers greater than or equal to 1:8 against various types of C. trachomatis were detected in these patients, whereas serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…In all cases the titers of IgA and IgM antibodies were low, while those of IgG were high in nearly half of the patients (46.7%). Similar or higher values of IgG antibodies were noted by Weidner et al [20] (40.5%) and Peeters et al [16] (49%), but lower were reported by Kojima et al [9] (7.5%) and Miyata et al [14] (29%). High titers of specific IgG antibodies as well as the presence of IgA antibodies in the serum provide evidence for an active, Chlamydia -induced pathological process.…”
Section: Discussionsupporting
confidence: 85%
“…In all cases the titers of IgA and IgM antibodies were low, while those of IgG were high in nearly half of the patients (46.7%). Similar or higher values of IgG antibodies were noted by Weidner et al [20] (40.5%) and Peeters et al [16] (49%), but lower were reported by Kojima et al [9] (7.5%) and Miyata et al [14] (29%). High titers of specific IgG antibodies as well as the presence of IgA antibodies in the serum provide evidence for an active, Chlamydia -induced pathological process.…”
Section: Discussionsupporting
confidence: 85%
“…Weidner et al [12] isolated Chlamydia from urethral swabs after prostatic massage in patients with Prostatitis is a common genitourinary disease in men. The National Institutes of Health has defined four types of prostatitis.…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…We applied the localization protocol of the four-specimen technique [5] and combined quantitative determinations of microorganisms [1,7] plus quantitative cytologic analysis [13,14] plus, in chlamydial infections, serologic investigations [12].…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…We examined 233 men with signs and symptoms of chronic prostatitis [ 12]. In 43 patients (18.3%) C. tracho matis was isolated from EPS.…”
Section: Role O F C Trachomatis In Prostatitismentioning
confidence: 99%